Multi-Objective Distribution feeder reconfiguration to improve transient stability, and minimize power loss and operation cost using an enhanced evolutionary algorithm at the presence of distributed generations. (March 2016) - Mahboubi-Moghaddam, Esmaeil; Narimani, Mohammad Rasoul; Khooban, Mohammad Hassan; Azizivahed, Ali; Javid sharifi, Mahshid
Highlights: This paper proposes a new modified multi-objective evolutionary algorithm. The proposed framework is simple and does not have complexities. The proposed approach is applied on Distribution feeder reconfiguration (DFR). The effectiveness of the proposed method is studied based on a typical 33-bus test system. Abstract: This paper proposes a multi-objective evolutionary algorithm method for Distribution feeder reconfiguration (DFR) with distributed generators (DG) in a practical system. Considering the low inertia constant of DG units in order to take the transient stability of DGs into account is one of the major issues in power systems. Especially when the penetration of DGs is low, the impacts of them on the distribution system transient stability may be neglected. However, when the penetration of DG increases, the transient stability of them must be taken into account (more DGs, more transient issues). To this end, the DFR problem has been solve by an enhanced Gravitational Search Algorithm (EGSA) to improve the transient stability index and decrease losses and operation cost in a distribution test system with multiple micro-turbines. The effectiveness of the proposed approach is studied based on a typical 33-bus test system. For getting close to the practical condition and considering the detailed dynamic models of the generators and other electric devices in power system, simulation and programming of this approach are done by the DIgSILENT® Power Factory software.